2011
DOI: 10.1189/jlb.0710404
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: CD45RB glycosylation is specifically regulated during human peripheral B cell differentiation

Abstract: A screen of cell surface markers differentially expressed during peripheral B cell differentiation identified that the CD45RB epitope detected by the mAb MEM-55 was highly expressed on CD27(+) memory B cells and absent on CD27(-) naïve B cells. IgG(+)CD27(-) memory and a previously unacknowledged CD27(-) population in blood also expressed high levels of CD45RB(MEM55). Naïve and memory B cells from tonsils followed the pattern observed in blood, and CD38(high) B cells had a bimodal expression pattern when analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 50 publications
8
57
0
Order By: Relevance
“…The splicing pattern of CD45 does not change during peripheral human B cell development, with the longest CD45RABC form being dominant at all stages. However, the expression of the CD45RB MEM55 epitope changes through developmentally regulated glycosylation in human B cells, with high expression on essentially all CD27 + B cells but not on naive or transitional B cells [81]. The CD45RB MEM55 epitope is also present on a minor population of CD27 ‐ B cells that express high levels of IgM (Fig.…”
Section: Cd45rbmem55 Is Expressed Differentially During B Cell Differmentioning
confidence: 97%
See 1 more Smart Citation
“…The splicing pattern of CD45 does not change during peripheral human B cell development, with the longest CD45RABC form being dominant at all stages. However, the expression of the CD45RB MEM55 epitope changes through developmentally regulated glycosylation in human B cells, with high expression on essentially all CD27 + B cells but not on naive or transitional B cells [81]. The CD45RB MEM55 epitope is also present on a minor population of CD27 ‐ B cells that express high levels of IgM (Fig.…”
Section: Cd45rbmem55 Is Expressed Differentially During B Cell Differmentioning
confidence: 97%
“…These include CD27 + IgM ‐ IgD + cells and CD27 ‐ class‐switched cells [71,73,80]. Recently, our group found that all memory B cell populations, but not naive cells, express CD45RB MEM55 , possibly making it a better marker for memory B cells than CD27 [81].…”
Section: Human B Cell Differentiation Stages and Lineages Present In mentioning
confidence: 99%
“…An alternative sorting strategy for separating B cells is to use CD24 and CD38, but the relationship with this strategy and that of using CD27/IgD is not clear cut and multiple subpopulations have differential expression of CD27, IgD, CD24, CD38, and B220 (Sanz et al, 2008). Recently, markers such as CD45RB MEM55 (Koethe et al, 2011) and CD330a (Silva et al, 2011) have been reported as alternative markers to help define human memory B cells. Whether they will prove more useful than current strategies remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…These memory subpopulations show different frequencies of somatic mutation and different replication histories that are thought to reflect their formation on primary or secondary germinal centres or outside germinal centre reactions [5]. A potential new marker for human memory B-cell subpopulations has been identified recently [6]. A proposal has been made that immunophenotyping of peripheral blood B cells should include the markers CD19, CD20, CD24, CD27, CD38 and IgD to be able to distinguish the major subpopulations [7].…”
Section: Introduction To B-cell Subpopulationsmentioning
confidence: 99%
“…A proposal has been made that immunophenotyping of peripheral blood B cells should include the markers CD19, CD20, CD24, CD27, CD38 and IgD to be able to distinguish the major subpopulations [7]. More detailed information including separation into further subsets and subtle differences in activation status that may be important when looking at disease states may require use of other markers such as different immunoglobulin isotopes, activation markers or chemokine receptors [6,8-14]. …”
Section: Introduction To B-cell Subpopulationsmentioning
confidence: 99%